Two new Clearwing moths from coastal Kenya (Lepidoptera: Sesiidae: Melittiini, Osminiini) - Bartsch, Daniel; Sáfián, Szabolcs (Zootaxa, 2025)
In this study, two new species of African Sesiidae are described from coastal Kenya. Melittia mida sp. nov. (Melittiini) from a series of eight males from Mida village at the edge of the Arabuko-Sokoke Forest, and Homogyna fenestra sp. nov. (Osminiini) from ten males collected across the Kenyan coast between the Dakatcha Woodland in the north and Diani beach in the south. Adults and male genitalia of both species are illustrated. Melittia mida sp. nov. is well characterized by the predominantly olive-brown body colour and the large transparent areas of the forewings. Homogyna fenestra sp. nov. differs from similar congeners by a transparent area distal to the forewing discal spot and by the completely transparent hindwings.